Evaluation of compatibility of file and gutta-percha cones in three different endodontic systems using scanning electron microscopy - Eskibağlar, Mehmet; Özata, Merve Yeniçeri; Ocak, Mevlüt Sinan; Öztekin, Faruk (Turkish Endodontic Society, 2023)
Purpose: The aim of this study was to evaluate the matching properties of the gutta-percha (GP) cones and different file systems with variable tapers. Methods: Fifteen files and GP cones TruNatomy Prime (TRN-P), WaveOne Gold Primary (WOG-P), and Reciproc Blue (Rec-B R25) systems were examined under a scanning electron microscope. Diameter measurements of files and GP cones were made from D1 to D16 using AutoCAD software. Data were analyzed with independent samples t-tests. Statistical significance was determined as p< 0.05. Results: The diameters of the file and GP cones were within the acceptable tolerance range. The file diameter was larger than the GP diameter at all points of incompatibility in the TRN-P system (p< 0.05). In the WOG-P group, the file diameter was wider up to the D10 level, while the GP cone diameter was wider at the D11 point and beyond p<0.05. In the Rec-B group, the file diameter was wider up to the D6 level, while the GP cone diameter was wider at the D7 point and beyond p<0.05. Conclusion: Three file systems are largely incompatible with the GP cones. In the TRN file system, unlike the other two groups, the GP cone had a narrower diameter than the file at each point. © 2023 Turkish Endodontic Society.
Keywords: Diameter; reciproc blue; rotary file systems; standardization; TruNatomy; WaveOne Gold